Práticas integrativas de cuidado numa abordagem de educação do espírito junto ao sujeito em situação de rua - Erbereli, Ligia Gomes Rodrigues (2020)
OBJECTIVES: This research aims to study the contributions of development care Integrative and Complementary Practices of a Spiritual Education approach by the Casa da Sopa Spiritual Group (GECS) with homeless people. The integrative practices studied in the approach were fluid therapy and microkinesitherapy. Thus, the specific objectives were established as: a) to check how fluid therapy is inserted within the mediation of Spiritual Education by GECS with homeless people; b) to check how microkinesitherapy, as a complementary practice to the ones already carried out by GECS, can contribute in the mediation of Spiritual Education by GECS with homeless people. METHOD: The qualitative approach was considered the most appropriate to apprehend the subjects’ symbolic universe, together with Existential Action-Research methodology by René Barbier. The research was inserted within the specific context of care provided by the Casa da Sopa Spiritist Group in Fortaleza. The medianimic device (MD) was used as a complementary data collection technique. RESULTS: The intervention proposed was carried out with six subjects. Both fluid therapy and microkinesitherapy contributed to the subjects’ making reflections about themselves, life, and their relation to the world, which were materialized in self-possessed movements that signaled advances in their spiritual educational paths. The integrative care practices acted in a dynamic manner in the process, sometimes dispersing information and fluids unnecessary to the organism, other times adding them. The assumption of their own educational trajectories proved to be fundamental. CONCLUSION: Educating the full being also involves partnership and care, included in the teaching and learning process. Therefore, the Integrative Care Practices studied proved to be important intervention tools in this sense, since they work through welcoming, subtle touch, dispersion and donation of magnetic and spiritual fluids, as well as information frequencies, so that to compose messages through verbal and non-verbal languages, which are fundamental when we take into account the physical, mental and spiritual dimensions, and the three floors of the mental house.